2021
DOI: 10.1002/alz.12462
|View full text |Cite
|
Sign up to set email alerts
|

Attention‐deficit/hyperactivity disorder and Alzheimer's disease and any dementia: A multi‐generation cohort study in Sweden

Abstract: Introduction:We examined the extent to which attention-deficit/hyperactivity disorder (ADHD), a neurodevelopmental disorder, is linked with Alzheimer's disease (AD) and any dementia, neurodegenerative diseases, across generations. Methods:A nationwide cohort born between 1980 and 2001 (index persons) were linked to their biological relatives (parents, grandparents, uncles/aunts) using Swedish national registers. We used Cox models to examine the cross-generation associations.Results: Among relatives of 2,132,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
2
19
1
1
Order By: Relevance
“…A second possibility is that the inclusion of non-ADHD cases in the exposed group is driving observed effects. As previously noted, many non-ADHD hyperkinetic disorders—which were included in the exposed cohort in four of the five cohort studies (Curtin et al, 2018 ; Tzeng et al, 2019 ; Du Rietz et al, 2021 ; Zhang et al, 2021 )—are caused by damage to the basal ganglia (Wichmann and DeLong, 2010 ) and may conceivably predispose one to further later-life basal ganglia dysfunction (a hallmark of LBD, e.g., McKeith et al, 2017 ). To tease apart these issues will require careful and systematic assessment of ADHD across all participants within future studies, and an examination of neurodegenerative disease risk in ADHD and non-ADHD hyperkinetic syndromes separately.…”
Section: Critical Appraisal Of Methodological Approachesmentioning
confidence: 90%
See 4 more Smart Citations
“…A second possibility is that the inclusion of non-ADHD cases in the exposed group is driving observed effects. As previously noted, many non-ADHD hyperkinetic disorders—which were included in the exposed cohort in four of the five cohort studies (Curtin et al, 2018 ; Tzeng et al, 2019 ; Du Rietz et al, 2021 ; Zhang et al, 2021 )—are caused by damage to the basal ganglia (Wichmann and DeLong, 2010 ) and may conceivably predispose one to further later-life basal ganglia dysfunction (a hallmark of LBD, e.g., McKeith et al, 2017 ). To tease apart these issues will require careful and systematic assessment of ADHD across all participants within future studies, and an examination of neurodegenerative disease risk in ADHD and non-ADHD hyperkinetic syndromes separately.…”
Section: Critical Appraisal Of Methodological Approachesmentioning
confidence: 90%
“…Strengths include well-powered analyses and extensive follow-up periods (>10 years) in most studies. However, six (Curtin et al, 2018 ; Fluegge and Fluegge, 2018 ; Tzeng et al, 2019 ; Fan et al, 2020 ; Du Rietz et al, 2021 ; Zhang et al, 2021 ) rely on ICD diagnostic codes extracted from electronic health records, and there are limitations around the validity and accuracy of these codes, particularly for a disorder that is notoriously difficult to detect in adults (Newcorn et al, 2007 ; Ginsberg et al, 2014 ). The remaining two (Walitza et al, 2007 ; Golimstok et al, 2011 ) are limited by potentially biased and inaccurate self-reported retrospective childhood ADHD symptoms in small samples of cognitively impaired participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations